Synthesis and Thermoelectric Characterization of Lead Telluride Hollow Nanofibers - Zhang, Miluo; Park, Su-Dong; Kim, Jiwon; Nalbandian, Michael; Kim, Seil; Choa, Yongho; Lim, Jaehong; Myung, Nosang V. (Frontiers in Chemistry, 2018)
Galvanic displacement reaction and electrospinning were combined to synthesize lead telluride (PbTe) hollow nanofibers with controlled surface morphology and dimension from cobalt nanofibers for the first time. By employing Co instead of Ni as the sacrificial material, residue-free PbTe nanofibers were synthesized. The Pb content of the PbTe nanofibers was slightly affected by the Pb2+ concentration in the electrolyte, while the average outer diameter increased with Pb2+ concentration. The surface morphology of PbTe nanofibers was strongly dependent on the diameter of sacrificial nanofibers where it altered from smooth to rough surface as the Pb2+ concentration increased. The temperature-dependent electrical conductivity and Seebeck coefficient of the as-synthesized nanofibers were systematically measured. Energy barrier height was found to be one of the key factors affecting the thermoelectric properties – that is, higher energy barrier heights increased the Seebeck coefficient, but lowered the electrical conductivity.